2020
DOI: 10.48550/arxiv.2003.01361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On shrinking targets and self-returning points

Abstract: We consider the set Rio of points returning infinitely many times to a sequence of shrinking targets around themselves. Under additional assumptions we improve Boshernitzan's pioneering result on the speed of recurrence. In the case of the doubling map as well as some linear maps on the d dimensional torus, we even obtain a dichotomy condition for Rio to have measure zero or one. Moreover, we study the set of points eventually always returning and prove an analogue of Boshernitzan's result in similar generalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…) is bounded away from 0 for large k, it is possible to find a K such that (35) holds for all large k. 10.2. Proof of Theorem 3.4 Case (2).…”
Section: Proof Of Theorem 34mentioning
confidence: 99%
“…) is bounded away from 0 for large k, it is possible to find a K such that (35) holds for all large k. 10.2. Proof of Theorem 3.4 Case (2).…”
Section: Proof Of Theorem 34mentioning
confidence: 99%
“…Theorem 1.1 was improved by who showed that the exponent α can be replaced by the lower local dimension of a measure at x. For piecewise C 2 expanding maps with the ergodic measure equivalent to Lebsgue measure, Kirsebom-Kunde-Persson [6] improved the speed in (1.1) from n to n(log n) θ with θ < 1/2.…”
Section: Introductionmentioning
confidence: 99%
“…As far as a general error function ψ is concerned, hardly anything is known. The only known results for µ-measure of R(ψ) are recently proven by Chang-Wu-Wu [4], Baker-Farmer [1], and Kirsebom-Kunde-Persson [6]. Chang-Wu-Wu [4] considered homogeneous self similar set satisfying the strong separation condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent improvements of Boshernitzan's result for particular classes of dynamical systems can be found in papers by Pawelec [12]; Chang, Wu and Wu [5]; Baker and Farmer [1]; Hussain, Li, Simmons and Wang [7]; and by Kirsebom, Kunde and Persson [9].…”
mentioning
confidence: 99%